Literatur Review: Efektivitas Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Siswa Abad 21 - Rika Lutfiana Sari; Natalia DM Silitonga; Ester Herwina Br Kaban; Jodion Siburian; Ali Sadikin; Fitri Astriawati (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The purpose of this study is to assess the effectiveness of differentiated learning on the learning outcomes of 21st century students through a literature review. This study uses a literature method from journals that have the subject of differentiated learning. The results of the literature show that differentiated learning can improve various aspects of student learning outcomes such as critical thinking skills, creativity, cognitive learning outcomes, learning motivation, and problem solving. It is concluded that the application of this learning has a positive impact on improving student learning outcomes in the 21st century.Abstrak: Tujuan dari penelitian ini untuk menilai efektivitas pembelajaran berdiferensiasi terhadap hasil belajar siswa abad ke-21 melalui tinjauan literatur. Penelitian ini menggunakan metode literatur dari jurnal yang memiliki pokok bahasan pembelajaran berdifernsiasi. Hasil dari literatur menunjukkan pembelajaran berdiferensiasi dapat meningkatkan berbagai aspek hasil belajar siswa seperti kemampuan berpikir kritis, kreatifitas, hasil belajar kognitif, motivasi belajar, dan problem solving. Disimpulkan bahwa penerapan pembelajaran ini berdampak positif terhadap peningkatan hasil belajar siswa di abad ke-21.